Interactive Multimedia Educational Games Based on Problem-Based Learning (PBL) for Ecosystem Material to Enhance Student Learning Motivation - Kadek Ayu Wahyuni; I Made Citra Wibawa; Kade Sathya Gita Rismawan (MIMBAR PGSD Undiksha, 2025)
Low learning motivation among elementary school students is often influenced by the limited use of interactive and contextual learning media. This study aims to design and develop interactive multimedia in the form of an educational game based on Problem-Based Learning (PBL), examine the validity of the developed product, analyze the practicality of the media within the learning context, and assess its effectiveness in improving students' learning motivation. This research is a type of Research and Development (R&D) utilizing the ADDIE development model and a One Group Pretest-Posttest experimental design. The study involved 24 elementary school students as research subjects. Data were collected through interviews, observations, and questionnaires using validated instruments. The data were analyzed using qualitative and quantitative descriptive analysis techniques. The results show that: (1) interactive multimedia in the form of a PBL-based educational game was successfully developed and meets the criteria for feasible learning media; (2) the content validity scores ranged from 0.875 to 1.00 (very high category), while media validity scores ranged from 0.625 to 1.00 (high to very high category); (3) the practicality of the media was rated 4.80 by teachers and 5.00 by students (very good category); and (4) the media’s effectiveness yielded a significance value of < 0.001, indicating a statistically significant increase in students' learning motivation between the pretest and posttest. These findings affirm that integrating interactive multimedia based on PBL into the learning process can foster a more engaging, creative, and meaningful learning experience, making it a promising innovative strategy to enhance elementary students’ learning motivation.